2019
DOI: 10.5463/dcid.v29i3.780
|View full text |Cite
|
Sign up to set email alerts
|

Compliance of Zimbabwean Hotels in the Provision of Innovative Facilities for Guests with Disabilities

Abstract: Purpose: In Zimbabwe, people with disabilities have limited options when looking for hotel accommodation as hotels often lack facilities that cater to their specific needs. This study sought to explore the perceptions of people with disabilities on the compliance of Zimbabwean hotels in the provision of innovative facilities for guests with disabilities.Methods: Data was collected by administering a semi-structured interview guide to 55 respondents. Thematic analysis of the data was carried out.Results: The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…A similar technique should be adapted in other sectors such as transport and attractions sectors. The technique will attract a significant number of disabled travellers because some of them are willing to pay any amount to get the desired experience (Mangwiro et al, 2018). For instance, having space between seats will not only assist wheelchair users to sit comfortably in public transports but will also offer a positive experience to people with mobility challenges (senior travellers, small kids, and pregnant women) since they put more emphasis on public transport more than other accessibility issues.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A similar technique should be adapted in other sectors such as transport and attractions sectors. The technique will attract a significant number of disabled travellers because some of them are willing to pay any amount to get the desired experience (Mangwiro et al, 2018). For instance, having space between seats will not only assist wheelchair users to sit comfortably in public transports but will also offer a positive experience to people with mobility challenges (senior travellers, small kids, and pregnant women) since they put more emphasis on public transport more than other accessibility issues.…”
Section: Discussionmentioning
confidence: 99%
“…But surprisingly, some of the providers thought there was no need to develop facilities that follow universal designs. Mangwiro et al (2018) assessed the perceptions of people with disabilities following the compliance of Zimbabwean hotels. Using thematic analysis, it was revealed that Zimbabwe was still lagging when it came to compliance of universally designed facilities, even though disabled people were willing to pay as much as was needed to get accessible facilities.…”
Section: Accommodation and Accessible Tourismmentioning
confidence: 99%
See 2 more Smart Citations
“…Apesar da questão sustentável, a literatura confirma que as PNE se tornaram um mercado importante para a indústria hoteleira. A crescente demanda de pessoas com deficiência é uma evidência para apoiar o potencial da indústria hoteleira de se beneficiar desse mercado emergente (Hussien & Jones, 2016;Mangwiro, Zengeni1, Mirimi & Chamunorwa1, 2018).…”
Section: Introductionunclassified